The Interaction between Heterotrophic Bacteria and Coliform, Fecal Coliform, Fecal Streptococci Bacteria in the Water Supply Networks - Nazak AMANIDAZ; Ali ZAFARZADEH; Amir Hossein MAHVI (Tehran University of Medical Sciences, 2015)
Background: This study investigated the interaction between heterotrophic bacteria and coliform, fecal coliforms, fecal streptococci bacteria in water supply networks. Methods: This study was conducted during 2013 on water supply distribution network in Aq Qala City, Golestan Province, Northern Iran and standard methods were applied for microbiological analysis. The surface method was applied to test the heterotrophic bacteria and MPN method was used for coliform, fecal coliform and fecal streptococci bacteria measurements. Results: In 114 samples, heterotrophic bacteria count were over 500 CFU/ml, which the amount of fecal coliform, coliform, and fecal streptococci were 8, 32, and 20 CFU/100 ml, respectively. However, in the other 242 samples, with heterotrophic bacteria count being less than 500 CFU/ml, the amount of fecal coliform, coliform, and fecal streptococci was 7, 23, and 11 CFU/100ml, respectively. The relationship between heterotrophic bacteria, coliforms and fecal streptococci was highly significant (P<0.05). We observed the concentration of coliforms, fecal streptococci bacteria being high, whenever the concentration of heterotrophic bacteria in the water network systems was high. Conclusion: Interaction between heterotrophic bacteria and coliform, fecal coliforms, fecal streptococci bacteria in the Aq Qala City water supply networks was not notable. It can be due to high concentrations of organic carbon, biofilms and nutrients, which are necessary for growth, and survival of all microorganisms.   Keywords: Heterotrophic bacteria, Coliform, Fecal coliforms, Fecal streptococci, Water networks